(untitled) (Gaceta Técnica, 2024)
This Correction is to clarify and replace the differences in the article in Gaceta Técnica, Volumen 25(2), 23-45, july-december, 2024 (https://revistas.uclave.org/index.php/gt/article/view/4820), between what was published and what the author subsequently sends as clarifications in order to proceed to publication. The Editorial Committee is not responsible for these differences